DESAIN INTERIOR HOTEL SYARIAH - Ahmad Fajar Ariyanto (Institut Seni Indonesia Surakarta, 2012)
Transformation to a sharia hotel has brough a different treatment for its interior design.Interior as an activity centre has to accomodate the hotel needs which meet with sharia ofIslam. This sharia hotel discourse has been developing, finding a fixed form, and tried toplace itself in anyway between policy, market, rule, and its ideology. As a cultural product, aninterior design can express the life style, ideology, and taste of their sociaty. Economically,the interior design takes part in improving the product quality as well as meeting the sociatytaste and finally it would be a centre to meet all the contradictions that suite in sociaty at large.Keywords : Sharia Hotel, Transformation, Interior Design